Relationship Among Digital Competence, Organizational Culture, Leadership Towards Digital Transformation Readiness, Study Case: Digital Transformation Program in PT XYZ Stamping Industries - Rahadyan Pramudito Kumarasakti; Achmad Fajar Hendarman (Green Publisher Indonesia, 2025)
In the current condition of a technology-based industry, the need to adapt towards a massive usage of technology is a must for a company. The usage of the technology will drive a different approach perspective on how a company will stand their ground to achieve the competitive advantage. Digital Transformation is becoming one of the most important things needed to be done by a company. The potential findings of this research were aimed to provide a new insight perspective for the Business Owner of PT Anugerah Stamping Industries about the factors that they needed to be concerned about to prepare their Employees about their Transformation Readiness. PT Anugerah Stamping Industries was facing a decreasing sales performance and an increasing operational cost due to the market competition, which led them to decide to take a Digital Transformation Program. The Research will use the quantitative methods of Multiple Linear Regression to map the Relationship between each of the independent variables towards the Dependent Variables, combined with a Qualitative approach by using an interview with the internal counterparts to discuss the findings. This paper will focus on discussing the Relationship between Digital Competence, Organisational Culture, and Leadership towards the Digital Transformation Readiness. The sample of this research is represented by the Employees, with a number of 106 employees out of 576 total population. This research shows there is a positive and significant relationship among Digital Competencies, Digital Organizational Culture, and Digital Leadership towards the Digital Transformation Readiness for the PT Anugerah Stamping Industries.